Moralumo iššūkis Carlo Schmitto politiškumo sampratai. - Jokubaitis, Alvydas (Problems / Problemos, 2020)
Schmitt makes a distinction between politics and the political; however, he does not speak about the distinction between morality and the moral. By introducing the concept of the moral, we aim to show the weak points of his critique of liberalism. The aim of the article is to look at Schmitt's concept of the political from the perspective of the moral. This helps to reveal previously unseen aspects of his theory. First, the ontology of the moral stands in direct competition with the ontology of the political. Secondly, the political is not a separate ontology because it depends on the primacy of anthropological presuppositions. Thirdly, Schmitt's concept of the political is paradoxically like the liberal stance of morality, which is the object of his critique.